Mengukur Kualitas Pelayanan Berbasis Preferensi Masyarakat pada Pemerintahan Daerah Berwilayah Kepulauan - Said, Moh; Cahyasari, Erlita (Jurnal Ilmiah Administrasi Publik, 2023)
The quality of public services is a manifestation of government performance, and measuring based on people's preferences. This study measured the quality of public services in Sumenep Regency using a quantitative descriptive method with five dimensions of measuring the quality of public services, namely reliability, responsiveness, assurance, empathy, and tangible that operate by  nine elements of measuring community satisfaction of public service from the Regulation of the Minister of Administrative Reform and Bureaucratic Reform Number 14 of 2017 concerning Guidelines for Compiling Public Satisfaction Surveys for Public Service Provider Units. The results of the study show that the quality of public services is still not optimal, where there are still many service elements that require quality improvement. Some elements that show a low index value are the quality-of-service facilities and infrastructure, the services time, service procedures, the suitability of standards, and the competence of personnel. Recommendations for improving service quality in Sumenep Regency are prioritized based on the ranking of all service elements. Another finding is there is a gap in the quality of public service delivery between mainland and island regions, with the island regions having lower quality, thus requiring special attention from the Sumenep Government